Hubungan Karakteristik Ibu Hamil TM Tiga Dengan Kecemasan Ibu Menghadapi Persalinan Di Metro - Martini, Martini; Oktaviani, Ika (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2016)
Pregnancy is a dramatic episode of biological condition, psychological changes, and adaptation of a woman who never experienced it. Most women assume that pregnancy is natural that must be passed, but some regard it as an event that determines the next life. Worry and anxiety in pregnant women if not treated seriously will have an impact and influence on the physical and psychic, both in the mother and fetus. The aim of research to determine the relationship between the characteristics of third trimester pregnant women (age, gravidity, education level, occupation, and health status) with anxiety in the face of labor. This Reseach use cross sectionalstudy design. The research location in BPM Ch. Sudilah Ganjaragung Metro City Lampung Indonesia The study population of pregnant women TM III as 55orang. The sampling technique uses accidental sampling. The collection of data carried out in July s / d in August 2016. The instrument used is the Zung Self-Rating Anxiety Scale (ZSAS) to measure the level of anxiety in the third trimester pregnant women in the face of labor. Analysis using the chi-Square test. The results showed that of the 55 respondents, 52.7% of pregnant women do not experience anxiety and 47.3% of pregnant women experience anxiety. Of the five variables studied, the two variables was not able to prove their relationship, such as age (p = 0.568), occupation (p = 0592), while the other variables are gravidity (p = 0.022) and educational level (p = 0.047) and health status (p = 0.010) were statistically prove the existence of a significant relationship with anxiety in the face of labor. The researchers suggest that health workers, especially midwives as health care providers provide counseling to pregnant women after examination that aims to pregnant women can avoid the anxiety in the face of labor Pregnancy is a dramatic episode of biological condition, psychological changes, and adaptation of a woman who never experienced it. Most women assume that pregnancy is natural that must be passed, but some regard it as an event that determines the next life. Worry and anxiety in pregnant women if not treated seriously will have an impact and influence on the physical and psychic, both in the mother and fetus. The aim of research to determine the relationship between the characteristics of third trimester pregnant women (age, gravidity, education level, occupation, and health status) with anxiety in the face of labor. This Reseach use cross sectionalstudy design. The research location in BPM Ch. Sudilah Ganjaragung Metro City Lampung Indonesia The study population of pregnant women TM III as 55orang. The sampling technique uses accidental sampling. The collection of data carried out in July s / d in August 2016. The instrument used is the Zung Self-Rating Anxiety Scale (ZSAS) to measure the level of anxiety in the third trimester pregnant women in the face of labor. Analysis using the chi-Square test. The results showed that of the 55 respondents, 52.7% of pregnant women do not experience anxiety and 47.3% of pregnant women experience anxiety. Of the five variables studied, the two variables was not able to prove their relationship, such as age (p = 0.568), occupation (p = 0592), while the other variables are gravidity (p = 0.022) and educational level (p = 0.047) and health status (p = 0.010) were statistically prove the existence of a significant relationship with anxiety in the face of labor. The researchers suggest that health workers, especially midwives as health care providers provide counseling to pregnant women after examination that aims to pregnant women can avoid the anxiety in the face of labor Keywords: pregnancy, trimester III, anxiety